ANALISIS SOSIAL MASALAH HAMIL DILUAR NIKAH - Arniati; Sri yunita Taligansing, Marsanda Y Ice, Satria Sunai, Siti Nur Ain Napu, Sry Meylina, Abd Rahman Bik (ADISAM PUBLISHER, 2026)
This study aims to analyze the social phenomenion of out-of-wedlock pregnancy among adolescents,including its causes and impacts on society. The research method used is qualitative with a phenomenological approach, focusing on the experiences of female adolescents aged 15-18 who experienced pregnancy outside marriage. The results show that the main contributing factors include free association, lack of parental supervision, limited sexual education, and environmental influences,including social policies such as online learning. The impacts include social stigma, school dropout,economic difficulties, and legal issues related to the child's status. Efforts to address this issue often involve early marriage or unregistered (siri) marriage, which is considered valid in religious terms but creates legal problems in Indonesia. Therefore, active roles of families, education, and counseling services are needed to prevent and address this issue in accordance with social and religious norms.